Usability Evaluation of Wedding Administrative Information System using System Usability Scale - Hasibuan, Novrisyah; Putri, Raissa Amanda (Politeknik Ganesha Medan, 2022)
The Marriage Administration Information System at the Religious Affairs Office of Lubuk Barumun District is a system that is run by the Admin of the Religious Affairs Office of Lubuk Barumun District and the Community in Lubuk Barumun District. The main function provided by this marriage administration information system is to facilitate the Religious Affairs office in compiling data and delivering information to the public, this system can also facilitate the public in submitting marriage requirements and reconciliation files. In using the marriage administration information system, some people are still confused in running this marriage administration information system. Therefore, this study aims to evaluate the usefulness of the marriage administration information system using the System Usability Scale (SUS) method to determine the extent of the effectiveness, efficiency and satisfaction of using the marriage administration information system that has been built.